2006
DOI: 10.1109/tdei.2006.247822
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectrets from thermo-formed bubble structures of fluoropolymer-electret films

Abstract: Cellular and porous polymers with internal bipolar space charge can exhibit large piezoelectric thickness coefficients and have therefore led to significant advances in the understanding and the application of piezoelectricity in polymer electrets. As possible alternatives to these cellular ferroelectrets, other potentially useful configurations of space-charge electrets, such as bi-layer or multi-layer stacks of at least one "soft" porous and one "hard" non-porous electret film have been suggested and investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…It was also found that the d 33 -coefficient of piezoelectrets decreases slowly throughout the infrasonic, audio, and ultrasonic frequency ranges due to the increase of Young's modulus in this region [14,15]. The d 33 -coefficients of ferroelectrets have been further increased by pressure expansion methods [16,17], while the thermal stability of the piezoelectric effect was improved by using layered arrangements based on fluoropolymer films, where the air enclosures consist either of voids between the layers or of air volumes in a porous layer [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the d 33 -coefficient of piezoelectrets decreases slowly throughout the infrasonic, audio, and ultrasonic frequency ranges due to the increase of Young's modulus in this region [14,15]. The d 33 -coefficients of ferroelectrets have been further increased by pressure expansion methods [16,17], while the thermal stability of the piezoelectric effect was improved by using layered arrangements based on fluoropolymer films, where the air enclosures consist either of voids between the layers or of air volumes in a porous layer [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…So far, ferroelectrets have been successfully developed with poly(ethylene terephthalate), 41,42 poly(ethylene naphthalene-2,6-dicarboxylate), 43,44 cyclo-olefine copolymers, 45 and fluoropolymers. 35,[46][47][48][49] The consequences of plasma-polymer interactions might be different for different polymers. For example, an oxygen-plasma treatment of polytetrafluoroethylene can improve the stability of a negative charge.…”
Section: Reduced Stability Of the Piezoelectricity: A Detrimental mentioning
confidence: 99%
“…[10,11] and references cited therein), since they usually show ferroelectric-like behavior such as a polarization-voltage hysteresis as well as significant piezoelectricity. The piezoelectricity is directly related to the charge-storage properties of the polymer films and to the charging conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, voided structures were prepared by means of thermal fusion of various polymers, which resulted in multilayer piezoelectrets from fluoroethylenepropylene (FEP) and polytetrafluoroethylene (PTFE) films with piezoelectric activities comparable to the ferroelectret foams [11,18]. The two approaches essentially rely on molding several dome-shaped semi-bubbles into a fluoropolymer film and then fusing it to another flat polymer film, thus creating closed and more or less hemispherical voids.…”
Section: Introductionmentioning
confidence: 99%